Strategi Survival Usaha Mikro Kecil Menengah Batik Tulis Pekalongan di Tengah Pandemi Covid-19 (Studi Kasus pada “Batik Pesisir” Pekalongan) - Mohammad Rosyada; Anah Wigiawati (Institut Agama Islam Negeri Parepare, 2020)
The Corona virus pandemic is not just a health disaster, the virus known as Covid-19 has caused chaos in the economic sector. Not only large industries, the Corona virus pandemic has made MSME players in Indonesia nervous. The existence of MSMEs, whose role has contributed significantly to the economic rate, has not been affected by the Covid-19 outbreak. Pekalongan Coastal Batik as one of Pekalongan's written batik MSMEs has also felt the impact of this Covid-19. This research was conducted to find out how the survival strategy carried out by Batik Pesisir Pekalongan can still exist and survive in the midst of the Covid-19 pandemic that has hit Indonesia. This study uses a qualitative method with a case study approach. From the results of this study, it can be seen that in running its business,